2018
DOI: 10.1002/jcp.27638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of luteolin on canine osteosarcoma: Suppression of cell proliferation and synergy with cisplatin

Abstract: Canine osteosarcoma is characterized by aggressiveness, easy metastasis to the lungs, and high mortality after standard therapy. Luteolin is a flavonoid found in vegetables and fruits and has diverse functions. Elucidation of the biological mechanisms of luteolin on canine osteosarcoma will enhance the efficacy of chemotherapeutic agents in canine tumors. In this study, we examined the effects of luteolin in the canine osteosarcoma cell lines, D17 and DSN. The results of this study show that luteolin inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
(41 reference statements)
0
8
0
1
Order By: Relevance
“…Luteolin is a natural flavonoid found in many plants, such as carrots, broccoli, perilla leaves, and celery. Luteolin has a variety of biological effects, such as anti-inflammatory, antioxidant, and antitumor [ 16 18 ]. Recent studies have found that many flavonoids can inhibit EMT.…”
Section: Introductionmentioning
confidence: 99%
“…Luteolin is a natural flavonoid found in many plants, such as carrots, broccoli, perilla leaves, and celery. Luteolin has a variety of biological effects, such as anti-inflammatory, antioxidant, and antitumor [ 16 18 ]. Recent studies have found that many flavonoids can inhibit EMT.…”
Section: Introductionmentioning
confidence: 99%
“…LUT has various biological functions such as being anti-inflammatory [14], antiatherogenic [15], and having antitumor effects [16]. In addition, LUT was shown to reduce proliferation and induce apoptosis in human osteosarcoma cells by regulating the apoptotic proteins BCL-2, BAX, caspase-3, and survivin [17]. Nevertheless, the biological functions and intracellular mechanisms of LUT in gastric cancer have not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It is derived from mesenchymal cells with osteogenic potential [2][3][4][5] . The lack of obvious early symptoms and high metastasis of osteosarcoma also result in high mortality and disability rates 26 . For osteosarcoma, common treatments such as limb salvage, radiotherapy, and chemotherapy have limited efficacy 27 .…”
Section: Discussionmentioning
confidence: 99%